RELIABILITY - BASED DESIGN OF REINFORCED CONCRETE TWO-WAY SOLID SLABS USING EUROCODE 2 (Nigerian Journal of Technology, 2014)
In this work, a FORTRAN-based computer program was developed to aid the design of reinforced concrete slabs to Eurocode 2 (EC 2)[1]design requirements at constant reliability levels using First Order Reliability Method (FORM).The design variables for the design of the slab were considered random with safety indices calculated using FORM. It was shown among other findings that the FORM design procedure gave more economical designs considering the area of steel required and final depth of section, than the EC 2 design procedure when a target safety level of 3.0 was considered. Also, example of design using the program was included for various values of target safety indices at constant geometrical, loading and end condition of the slab. The developed program is therefore suitable for application.  http://dx.doi.org/10.4314/njt.v33i4.3